Mortality risk in chronic Chagas cardiomyopathy: a systematic review and meta‐analysis. (30th October 2021) - Chadalawada, Sindhu; Rassi, Anis; Samara, Omar; Monzon, Anthony; Gudapati, Deepika; Vargas Barahona, Lilian; Hyson, Peter; Sillau, Stefan; Mestroni, Luisa; Taylor, Matthew; da Consolação Vieira Moreira, Maria; DeSanto, Kristen; et al.
Abstract: Aims: This study aimed to estimate the annual mortality risk and its determinants in chronic Chagas cardiomyopathy. Methods and results: We conducted a systematic search in MEDLINE, Web of Science Core Collection, Embase, Cochrane Library, and LILACS. Longitudinal studies published between 1 January 1946 and 24 October 2018 were included. A random‐effects meta‐analysis using the death rate over the mean follow‐up period in years was used to obtain pooled estimated annual mortality rates. Main outcomes were defined as all‐cause mortality, including cardiovascular, non‐cardiovascular, heart failure, stroke, and sudden cardiac deaths. A total of 5005 studies were screened for eligibility. A total of 52 longitudinal studies for chronic Chagas cardiomyopathy including 9569 patients and 2250 deaths were selected. The meta‐analysis revealed an annual all‐cause mortality rate of 7.9% [95% confidence interval (CI): 6.3–10.1; I 2  = 97.74%; T 2  = 0.70] among patients with chronic Chagas cardiomyopathy. The pooled estimated annual cardiovascular death rate was 6.3% (95% CI: 4.9–8.0; I 2  = 96.32%; T 2  = 0.52). The annual mortality rates for heart failure, sudden death, and stroke were 3.5%, 2.6%, and 0.4%, respectively. Meta‐regression showed that low left ventricular ejection fraction (coefficient = −0.04; 95% CI: −0.07, −0.02; P  = 0.001) was associated with an increased mortality risk. Subgroup analysis based on American Heart Association (AHA) classification revealed pooled estimate rates of 4.8%, 8.7%, 13.9%, and 22.4% ( P  < 0.001) for B1/B2, B2/C, C, and C/D stages of cardiomyopathy, respectively. Conclusions: The annual mortality risk in chronic Chagas cardiomyopathy is substantial and primarily attributable to cardiovascular causes. This risk significantly increases in patients with low left ventricular ejection fraction and those classified as AHA stages C and C/D.